Virtual Reality Trends as a Tool for Science Learning Revolution in the 21st Century: A Systematic Review - Arie Wahyu Prananta; Ruth Rize Paas Megahati S; Sudirman; Liza Yuliana (Jurnal Penelitian Pendidikan IPA, 2025)
VR educational multimedia systems have demonstrated their ability to improve teaching and learning efficiency through the provision of visual and interactive elements that accommodate a variety of learning preferences. This study aims to analyze and explore various research publications that investigate the use of virtual reality as a tool for the educational revolution in higher education. The research method used is a systematic literature review (SLR). The stages of this study include formulating research questions, searching for articles according to the research theme, identifying articles, screening articles, selecting potential articles, analyzing and synthesizing qualitative findings, and preparing a research report. The study yielded 21 potential articles that reflect the most recent research findings. The study's findings indicate that VR has the potential to revolutionize higher education by offering immersive learning experiences that captivate students in ways that conventional approaches cannot. This study highlights the growing interest in the application of VR technology in educational settings. The implications of this study emphasize the role of VR as a tool for the educational revolution in higher education, while also highlighting the need for careful implementation, ongoing research, and investment in technology and training to maximize its benefits.